Kemampuan Isolat Bakteri Pendegradasi Lipid dari Instalasi Pengolahan Limbah Cair PPKS PTPN-XIII Ngabang Kabupaten Landak - Ahmad Mulyadi, Wilhelmus Januar, Siti Khotimah, (Jurnal Protobiont, 2013)
Liquid wastes from palm oil containing lipid which, if not managed properly could potentially contaminate the environment. One of effective waste treatments that relatively cheap and environmentally friendly is by using bacteria as agents of biodegradation. The purpose of this study was to acquire lipid degrading bacteria and verify the isolate ability of lipid degrading bacteria which derived from sewage treatment plants PPKS PTPN XIII Ngabang, Landak District. The research was conducted from September 2011 to March 2012 at the laboratory of Microbiology and Chemistry laboratory of the Faculty of Mathematics and Natural Sciences, Tanjungpura University. The method used for isolation of bacteria was pour plate and streak plate. The results obtained 9 isolates of lipid degrading bacterium. LSWJ1 bacterium isolate were capable to degrade lipids better since they could grow in liquid media oily and had the ability to reduce lipid levels by up to 25% for 14 days. Identification showed that isolate belonged to the genus Bacillus.